AMBIGUITAS STATUS HUKUM PEKERJA MIGRAN ILEGAL SEBAGAI PELANGGARAN HUKUM ATAU KORBAN EKSPLOITASI - Intan, Dian Mustika; Harmain, Irfan; Kaloko, Ilhamda Fattah (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
This study examines the legal status ambiguity of Indonesian illegal migrant workers, positioning them as both legal violators and victims of exploitation, with a focus on the tension between normative compliance and human rights protections. Employing a normative legal research method, the article analyzes the misalignment between national regulations such as Law No. 18/2017, which restricts protections to legally documented migrant workers and international instruments, including the 1990 CMW Convention and the 2000 Palermo Protocol, which guarantee fundamental rights regardless of legal status. Key findings reveal systemic contradictions: while illegal migrant workers technically violate immigration laws, they are frequently subjected to structural exploitation (forced labor, human trafficking, and violence) due to inadequate legal safeguards. The study’s novelty lies in identifying a protection paradox: national legal frameworks exacerbate vulnerabilities through punitive approaches, whereas international human rights norms demand restorative, victim-centered responses. The analysis not only highlights normative inconsistencies but also underscores practical implications for migration governance, such as victim criminalization, inaccurate data, and barriers to prosecuting trafficking networks. The research recommends harmonizing national-international laws, adopting a victim centered approach, and strengthening interagency coordination to resolve legal ambiguities and ensure substantive justice for illegal migrant workers. These findings stress the urgency of shifting policy from security centric frameworks to human rights-based paradigms in addressing irregular migration.